Investigating the Pass-Through Effect of Global Oil Price Shock on Domestic Inflation in Selected African Countries - Lukman O. Oyelami; Babatunde S. Adekunle; Ademisola M. Oluwakemi (Croatian Economic Survey)
The large-scale war between Russia and Ukraine has increased global oil prices, signaling a new era of macroeconomic shock management for both developed and developing countries. Consequently, this study investigates the passthrough effect of oil prices on domestic inflation in selected African countries in a single estimation framework using the global vector autoregressive (GVAR) estimation technique. To achieve the objective of this study, country-specific data were gathered from twenty-one African countries and four foreign countries selected based on trade relations. The results from our estimation demonstrate that the domestic general price level in African countries responds to global oil price shocks. Also, like any other part of the world, a disparity-like response is observable for African countries. This is tightly connected to whether the country is a metal-resource-rich, non-rich resource, or oil-rich country. The study thus concludes that positive shocks in the global price of crude oil will worsen the delicate position of the domestic general price level in non-oil-producing African countries. Efforts to minimize the impact of international oil shocks in these countries should center around investment in renewable energy and stabilization of the economy’s supply side through proactive and effective macroeconomic management.